EFFECT OF OBSERVATION SYMBOL GRANULARITY ON SIGNATURE CLASSIFICATION ACCURACY - Bharadi, Vinayak A.; Chavan, Manoj (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Observation symbol granularity plays a crucial role in the accuracy of Hidden Markov Model (HMM)-based classification systems. In the context of online signature verification, the number of quantized observation symbols directly impacts the model’s capacity to capture subtle variations in user signatures. This paper investigates how varying symbol counts—from 200 to 750—influences classification accuracy, Equal Error Rate (EER), and convergence behavior. Using the SVC 2004 dataset and Hybrid Wavelet Transform (HWT)-derived pressure features, we analyze system performance across five symbol scaling intervals. Results indicate that a moderate symbol granularity (300–400) achieves optimal EER with efficient convergence and lower overfitting risks. These findings inform model tuning for signature-based biometric authentication systems.